Cystic fibrosis in the United Arab Emirates : a spatial, medical and historical perspective : a dissertation submitted for the degree of Master of Science to Massey University - Dawson, Kenneth (Massey University, 1999)
The aim of this dissertation is to report our observations on the disease, Cystic Fibrosis (CF) as it presents in the United Arab Emirates (UAE). It contains the first full clinical reports of how the disease manifests itself in the UAE, it defines the molecular basis for the disease and establishes a population frequency of gene carriage. The observations are made in light of the new knowledge of CF gene mutations, the spatial and ethnic aspects revealed by these findings and the creation of a new geography related to cystic fibrosis. The intention is to further hypothesise as to the spread of CF to the UAE and postulate as to the prior and subsequent events in relation to the spread of gene mutations elsewhere. Methods A wide range of methodologies have been applied. The original observations, as to the existence of CF in the Emirates were made in the Children's wards and outpatient clinics of Tawam Hospital, Al Ain, UAE. Subsequently, within the Faculty of Medicine in the UAE University, were developed the techniques required for specific gene mutational analyis. These were developed in conjunction with, and validated by, the Laboratoire de Genetique Molecularie in Paris, France. This was in collaboration with Dr Emmanuelle Girodon and her team. Individual methods are described in each chapter as appropriate.
Keywords: United Arab Emirates; Cystic fibrosis; Genetic aspects